Therapeutic Potential of Phytomedicines and Novel Polymeric Strategies for Significant Management of Candidiasis - Rohilla, Surbhi; Bhatt, D.C.; Gupta, Aditi (Current Pharmaceutical Design, 2018)
Background: Candidiasis is one of the most common opportunistic fungal infections caused by genus Candida. The genus is composed of around 200 species. The most virulent among all are, Candida albicans followed by various nonalbicans species. Despite various treatments available, the incidence of severe systemic fungal infections is increasing, and with it the related morbidity and mortality, in relation to the misuse of antimicrobials and the emergence of drug-resistant fungal species. Therefore, various novel therapeutic approaches need to be developed and explored to overcome these limitations and effective management of candidiasis. Objective: In this review, we focused on natural herbal remedies and significance of novel formulation approaches for the treatment of candidiasis. Conclusion: The reported studies suggested the promising role of phytomedicines and novel polymeric drug delivery systems in therapeutic management of candidiasis. Phytomedicines are effective substitutes of synthetic drugs as they are inexpensive with lesser number of side effects. Various novel particulate approaches can be successfully used to reduce fungal burden at the target site.
Keywords: antifungal agents